2023
DOI: 10.1002/fft2.288
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides from brown seaweed: Physicochemical properties, absorption in the intestine, and beneficial effects on intestinal barrier

Abstract: The intestinal barrier is critical in maintaining gut homeostasis and host health. The intestinal barrier dysfunction contributes to intestinal and systemic diseases like inflammatory bowel disease, colorectal cancer, and metabolic syndromes. This review summarizes the physicochemical properties of three main kinds of brown seaweed polysaccharides (BSP), laminarin, fucoidan, and alginate, along with their absorption and metabolism in the intestine and their effects on the intestinal barrier. The physicochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…UV radiation can trigger a cellular inflammatory response by stimulating the release of cytokines, chemokines, and other inflammatory mediators in the epidermis [ 55 ]. The release of pro-inflammatory cytokines increases the permeability of cell capillaries, leads to the infiltration and activation of inflammatory cells such as macrophages and neutrophils, causes inflammatory damage to the skin, and ultimately results in skin photoaging [ 56 ]. Studies have shown that UV irradiation can induce the release of pro-inflammatory cytokines such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) by keratinocytes, thereby disrupting collagen synthesis and interfering with ECM metabolism [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…UV radiation can trigger a cellular inflammatory response by stimulating the release of cytokines, chemokines, and other inflammatory mediators in the epidermis [ 55 ]. The release of pro-inflammatory cytokines increases the permeability of cell capillaries, leads to the infiltration and activation of inflammatory cells such as macrophages and neutrophils, causes inflammatory damage to the skin, and ultimately results in skin photoaging [ 56 ]. Studies have shown that UV irradiation can induce the release of pro-inflammatory cytokines such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) by keratinocytes, thereby disrupting collagen synthesis and interfering with ECM metabolism [ 57 ].…”
Section: Resultsmentioning
confidence: 99%